The just is by nature, not by convention. Stoic arguments against slavery and the doctrine of οἰκείωσις (Circe de clásicos y modernos, 2018)
This essay argues that the Stoic thesis of natural equality among human beings presupposes a radical reconsideration of the notion of nature, probably inspired on Antiphon the sophist. Even though the Stoics seem to consider the Antiphontean naturalism, focused on bodily faculties, and recognize the “conventional-natural” classical distinction applied to the difference between Greeks and barbarians, they develop the theory of natural equality toward a theory of justice and natural law that exceeds the identity of nature understood as bodily necessity. The author also maintains that this development is based on the Stoic thesis of familiarization.
Keywords: Antiphon; Stoicism; slavery; familiarization